2020
DOI: 10.3390/microorganisms8010132
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles against Foodborne Bacteria. Effects at Intestinal Level and Health Limitations

Abstract: Foodborne diseases are one of the factors that endanger the health of consumers, especially in people at risk of exclusion and in developing countries. The continuing search for effective antimicrobials to be used in the food industry has resulted in the emergence of nanotechnology in this area. Silver nanoparticles (Ag-NPs) are the nanomaterial with the best antimicrobial activity and therefore, with great potential of application in food processing and packing. However, possible health effects must be proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 120 publications
(138 reference statements)
1
62
0
3
Order By: Relevance
“…The antibacterial properties of biogenic Ag-NPs may be attributed to different mechanisms, such as charge influence of Ag-NPs. The partial dissolution of the bacterial cell membrane may be achieved due to the electrostatic attraction between the negative charge of the cell wall and the positive charge of the silver nanomaterial or by the interaction of nano-scaled silver with phosphorylated or sulfur proteins of the bacterial cell wall, causing the destabilization and depolarization of bacteria membrane to lose its integrity and leakage of H + [ 67 ]. Anther mechanism of biological toxicity of Ag-NPs could be attributed to the release of Ag + through oxidation process.…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial properties of biogenic Ag-NPs may be attributed to different mechanisms, such as charge influence of Ag-NPs. The partial dissolution of the bacterial cell membrane may be achieved due to the electrostatic attraction between the negative charge of the cell wall and the positive charge of the silver nanomaterial or by the interaction of nano-scaled silver with phosphorylated or sulfur proteins of the bacterial cell wall, causing the destabilization and depolarization of bacteria membrane to lose its integrity and leakage of H + [ 67 ]. Anther mechanism of biological toxicity of Ag-NPs could be attributed to the release of Ag + through oxidation process.…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial efficacy of Ag-NPs could be attributed to the binding of silver with the bacterial cell wall through electrostatic attraction between the positive charge of Ag-NPs and the negative charge of the cell wall. This electrostatic attractions destroys the selective permeability via the reacting of Ag-NPs with sulfur and phosphorylated proteins located in the bacterial cell wall causing partial dissolution of the cell membrane [ 48 ]. Nanoparticles enter the cell and causes the liberation of Ag + , which causes enhancement of the reactive oxygen species (ROS) that destroys the enzymes involved in cellular respiration and are ultimately responsible for cell death [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that AgNPs enhance the antibacterial potential of antibiotics compared to the drugs alone [12,13]. Reports of the impact of AgNPs on human health are still not numerous and are inconclusive as stated in the review paper [14]. It has been show that toxicity also depends on the physicochemical properties of nanoparticles [15] so it might be difficult to compare between toxicity research of AgNPs with different shapes and sizes at different concentrations.…”
Section: Introductionmentioning
confidence: 99%